Bioremediation of Wastewater Contaminated with Dyes, Rhodamine B Using Alginate Immobilized Cell of Spirulina platensis - Wilasinee Sriputtho; Buppha Jongput; Suneerat Ruangsomboon (My University, 2024)
Bioremediation of wastewater contaminated with rhodamine B dyes using alginate immobilized cell of Spirulina platensis was studied. Factors affecting the dye adsorption such as pH, contact time, adsorbent dose, and initial dye concentration were investigated. The results showed that the optimum pH for dye adsorption was at 2 with an adsorption capacity of 0.86±0.00 mg/g. The adsorption was very rapid and reached equilibrium within 180 min with an adsorption capacity of 1.24±0.00 mg/g. Dye adsorption capacity by this alga was reduced at high adsorbent dose whereas the increase of initial concentration of dye increased the adsorption capacity. The adsorption isotherm correlated with Langmuir with the maximum adsorption capacity (qm) of 52.70±3.18 mg/g. Adsorption kinetic correlated with pseudo-second order. The adsorption rate limiting step were film diffusion rate and secondary rate of intraparticle diffusion. This study suggested that alginate immobilized cell of S. platensis can be applied for treatment of wastewater contaminated with rhodamine B.
Keywords: Rhodamine B; Langmuir adsorption model; Spirulina (dietary supplement); Biosorption; Adsorption and biosorption for pollutant removal